A DYNAMIC APPROACH FOR BRAIN TUMOR DETECTION USING EDGE DETECTION TECHNIQUE - J, Prabhaharan; K, Preetham; Shetty, Pavan Kumar; Shetty, Koushik V; Suthar, Dhiraj S (The journal of contemporary issues in business and government, 2021)
Image process is most typically victimized framework in medical imaging. A foundation uncovering is alive for its trustiness and warrant that delivers a stronger understanding of seeable representation within the applications of laptop modality, same prosy catching, confronting perception, and recording force succeed. Machine Learning and Deep Learning algorithms are principally victimized for analyzing the medical pictures which may make, stage and categorize the tumor into sub classes, coherent with that the identification would be through by the professionals. during this production, we've mentioned the technique that's used for tumor pre-processing, and sorting.